Enhancing understanding of colorectal cancer through public education at MHCC Clinic, Pontianak - Haryanto Haryanto; Yuyun Nisaul Khairillah; Indri Erwhani; Ditha Astuti Purnamawati; Annisa Rahmawati; Surtikanti Surtikanti; Tiara Amalia Mentari; Erlis Eka Fitriana (Universitas Muhammadiyah Magelang, 2024)
Colorectal cancer is a malignancy that affects the tissues of the last part of the large intestine. There are several risk factors for colorectal cancer, including environmental factors, genetics, and the level of inflammation in the intestine. The aim of this community service activity is to enhance public awareness about colorectal cancer to minimize its impact. Conducted at the Muhammadiyah Health Care Center (MHCC) Clinic, this service employed lectures and discussions to educate the public on colorectal cancer prevention. The results indicate an increase in public knowledge regarding colorectal cancer, with a percentage of 27.5% falling into the